Radar echo simulation of dynamically rotating wind turbine blades based on 3D scattering center - Tang, Bo; Xie, Huanghai; Liu, Gang; Zhang, Longbin; Shang, Zhiyu (Frontiers in Energy Research, 2023)
High-fidelity simulation of the radar echo from the wind turbine (WT)for accurate acquisition of Doppler features, is the key issue in addressing reradiation interference from the wind farm on the nearby radar station. In view of the limitation of the conventional scattering center-based equivalent model to reflect the complex surface of blades, it is difficult to simulate the rotating blades’ echo accurately with the existing algorithm. Therefore, we proposed a simulation method based on a 3D scattering center extraction to deal with it. First, the method of scattering center equivalence to blade scattering is used in order to reduce the modelling as well as the solution of electromagnetic scattering from the multi-space attitude of the blade, which is different from the existing algorithm. Since the geometry affects the parameters of the scattering center, an orthogonal matching pursuit greedy algorithm is used to extract the parameter of the 3D scattering center model. Therefore, the temporal correspondence between the scattering center and the blade motion characteristics is established, resulting in a reconstruction of the scattered field data of the rotating blades. Consequently, the real-time simulation and Doppler characterisation of blades echoes are achieved using the Short Time Fourier Transform (STFT). A comparison of the results with the data obtained from the GTD scattering center model verifies the accuracy of the proposed method.